T Helper 1 Cellular Immunity Toward Recoverin Is Enhanced in Patients With Active Autoimmune Retinopathy - Lundy, Steven K.; Nikoopour, Enayat; Karoukis, Athanasios J.; Ohara, Ray; Othman, Mohammad I.; Tagett, Rebecca; Jayasundera, K. Thiran; Heckenlively, John R. (Frontiers in Medicine, 2018)
Autoimmune retinopathy (AIR) causes rapidly progressive vision loss that is treatable but often is confused with other forms of retinal degeneration including retinitis pigmentosa (RP). Measurement of anti-retinal antibodies (ARA) by Western blot is a commonly used laboratory assay that supports the diagnosis yet does not reflect current disease activity. To search for better diagnostic indicators, this study was designed to compare immune biomarkers and responses toward the retinal protein, recoverin, between newly diagnosed AIR patients, slow progressing RP patients and healthy controls. All individuals had measurable anti-recoverin IgG and IgM antibodies by ELISA regardless of disease status or Western blot results. Many AIR patients had elevated anti-recoverin IgG1 levels and a strong cellular response toward recoverin dominated by IFN. RP patients and controls responded to recoverin with a lower IFN response that was balanced by IL-10 production. Both AIR and RP patients displayed lower levels of total peripheral blood mononuclear cells that were due to reductions of CD4+ TH cells. A comparison of messenger RNA (mRNA) in whole blood indicated lower expression of ATG5 and PTPN22 and higher expression of several genes involved in TH cell signaling/transcription, and adhesion. These data indicate that an immune response toward recoverin is normal in humans, but that in AIR patients the balance shifts dramatically toward higher IFN production and cellular activation.